GeSn lateral p-i-n photodetector on insulating substrate - Xu, Shengqiang (2019)
We report the first experimental demonstration of germanium-tin (GeSn) lateral p-i-n photodetector on a novel GeSn-on-insulator (GeSnOI) substrate. The GeSnOI is formed by direct wafer bonding and layer transfer technique, which is promising for large-scale integration of nano-electronics and photonics devices. The fabricated GeSnOI photodetector shows well-behaved diode characteristics with high Ion/Ioff ratio of ~4 orders of magnitude (at ± 1 V) at room temperature. A cutoff detection beyond 2 µm with photo responsivity (Rop) of 0.016 A/W was achieved at the wavelength (λ) of 2004 nm.